Nomenclature and syntaxonomic notes on some high-rank syntaxa of the European grassland vegetation - Di Pietro, Romeo; Theurillat, Jean-Paul; Capelo, Jorge; Fernández-González, Federico; Terzi, Massimo; Čarni, Andraž; Mucina, Ladislav (Lazaroa, 2015)
We present descriptions of a new order (Ranunculo cortusifolii-Geranietalia reuteri and of a new alliance (Stachyo lusitanicae-Cheirolophion sempervirentis) for the herbaceous fringe communities of Macaronesia and of the southwestern Iberian Peninsula, respectively. A new alliance, the Polygalo mediterraneae-Bromion erecti (mesophilous post-cultural grasslands), was introduced for the Peninsular Italy. We further validate and typify the Armerietalia rumelicae (perennial grasslands supported by nutrient-poor on siliceous bedrocks at altitudes characterized by the submediterranean climate of central-southern Balkan Peninsula), the Securigero-Dasypyrion villosae (lawn and fallow-land tall-grass annual vegetation of Italy), and the Cirsio vallis-demoni-Nardion (acidophilous grasslands on siliceous substrates of the Southern Italy). Nomenclatural issues (validity, legitimacy, synonymy, formal corrections) have been discussed and clarified for the following names: Brachypodio-Brometalia, Bromo pannonici-Festucion csikhegyensis, Corynephoro-Plantaginion radicatae, Heleochloion, Hieracio-Plantaginion radicatae, Nardetea strictae, Nardetalia strictae, Nardo-Callunetea, Nardo-Galion saxatilis, Oligo-Bromion, Paspalo-Heleochloetalia, Plantagini-Corynephorion and Scorzoneret alia villosae.